An integrated adipose-tissue-on-chip nanoplasmonic biosensing platform for investigating obesity-associated inflammation. Issue 23 (10th October 2018) - Zhu, Jingyi; He, Jiacheng; Verano, Michael; Brimmo, Ayoola T.; Glia, Ayoub; Qasaimeh, Mohammad A.; Chen, Pengyu; Aleman, Jose O.; Chen, Weiqiang
Abstract : A biomimetic 'adipose-tissue-on-chip' integrated with nanoplasmonic biosensors for in situ multiplexed cytokine secretion analysis of obese adipose tissue. Abstract : Although many advanced biosensing techniques have been proposed for cytokine profiling, there are no clinically available methods that integrate high-resolution immune cell monitoring and in situ multiplexed cytokine detection together in a biomimetic tissue microenvironment. The primary challenge arises due to the lack of suitable label-free sensing techniques and difficulty for sensor integration. In this work, we demonstrated a novel integration of a localized-surface plasmon resonance (LSPR)-based biosensor with a biomimetic microfluidic 'adipose-tissue-on-chip' platform for an in situ label-free, high-throughput and multiplexed cytokine secretion analysis of obese adipose tissue. Using our established adipose-tissue-on-chip platform, we were able to monitor the adipose tissue initiation, differentiation, and maturation and simulate the hallmark formation of crown-like structures (CLSs) during pro-inflammatory stimulation. With integrated antibody-conjugated LSPR barcode sensor arrays, our platform enables simultaneous multiplexed measurements of pro-inflammatory (IL-6 and TNF-α) and anti-inflammatory (IL-10 and IL-4) cytokines secreted by the adipocytes and macrophages. As a result, our adipose-tissue-on-chip platform is capable of identifying stage-specific cytokine secretion profiles from a complex milieu during obesity progression, highlighting its potential as a high-throughput preclinical readout for personalized obesity treatment strategies.